Pengaruh Gaya Kepemimpinan, Motivasi, Dan Employee Relation Terhadap Kinerja Karyawan Pada PT. Perkebunan Nusantara Ii - Nanda Sitompul; Friska Handayani Silitonga; Liberting Gea; Kristi Endah Ndilosa Ginting; Mella Yunita (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to test and analyze the influence of Leadership Style, Motivation and Employee Relations on Employee Performance at PT. Perkebunan Nusantara II. This research method was carried out by conducting a survey by distributing questionnaires and direct interview methods to PT employees. Perkebunan Nusantara II. The total population and sample in this research was 100 employees. The results of partial hypothesis testing obtained a calculated t value < t table or 0.174 < 1.984 and the significance obtained was 0.863 > 0.05, the calculated t value > t table or 2.371 > 1.984 and the obtained significance was 0.020 < 0.05, the calculated t value < t table or 1.266 < 1.984 and the significance obtained was 0.209 < 0.05. This means that leadership style, motivation and employee relations simultaneously influence employee performance at PT. Perkebunan Nusantara II.